Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (Csr)(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011 - 2013) - Wardani, Agustian Wahyu; , Dr. Fatchan Ahyani, SE., M.Si (2016)
The purpose of this researche is to analyse the influence of the Characteristics Of Companies consisting of Firm Size (SIZE), Profitability (PROFIT), Leverage (LEV), Size of The Board of Commissioners (DK) And Growth (GROWTH) on the disclosure of Corporate Social Responsibility (CSR). Data from this study were obtained from manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2011 to 2013 for 48 companies with outlier 3 companies. Sampling by purposive sampling and hypothesis testing using multiple regression analysis. This result of this study indicate there is association between Profitability (PROFIT), Leverage (LEV), Size of the Board of ommissioners (DK) to Corporate Social Responsibility (CSR). But have no association between Company size (SIZE) and Corporate Growth (GROWTH) to Corporate Social Responsibility (CSR).